2014
DOI: 10.1088/1742-6596/547/1/012043
|View full text |Cite
|
Sign up to set email alerts
|

Natural convection in asymmetric triangular enclosures heated from below

Abstract: . Among a number of scientific topics he cultivated in his brilliant academic career, convection heat transfer was the first and the most beloved.Abstract. Triangular enclosures are typical configurations of attic spaces found in residential as well as industrial pitched-roof buildings. Natural convection in triangular rooftops has received considerable attention over the years, mainly on right-angled and isosceles enclosures. In this paper, a finite volume CFD package is employed to study the laminar air flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In attempts to model different weather scenarios, a number of studies have considered different thermal boundary conditions. Enclosure heated from below only is reported by Asan and Namli (2001), Mahmoudi (2011), Kamiyo et al (2014) and Cui et al (2019). Enclosure heated from above only is studied by Akinsete and Coleman (1982), Asan and Namli (2000) and Amrani et al (2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In attempts to model different weather scenarios, a number of studies have considered different thermal boundary conditions. Enclosure heated from below only is reported by Asan and Namli (2001), Mahmoudi (2011), Kamiyo et al (2014) and Cui et al (2019). Enclosure heated from above only is studied by Akinsete and Coleman (1982), Asan and Namli (2000) and Amrani et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, with the development of advanced numerical methods that could accurately predicted problems of flows in enclosed surfaces, majority of the authors have used modelling approach. In the past decade, the numerical modelling studies reported include those of , , Ching et al (2012), Yesiloz and Aydin (2013), Kamiyo et al (2014), Mirabedin (2016) and Amrani et al (2017) while the few experimental studies are those of Anderson et al (2010), Oztop et al (2012), Yesiloz and Aydin (2013), Raj et al (2018) and Michels et al (2018). In most cases, sealed attics are considered but there are few reports on vented attics , , Raj et al (2018)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mirabedin [3] formulated a correlation for Nusselt number in terms of its aspect ratio and Rayleigh number in case of a triangular enclosure and found that the Nusselt number increased with increase in aspect ratio. Kamiyo et al [4] studied the heat transfer in an asymmetric triangular enclosure with a hot isothermal base wall. They varied the pitch angle (angle between the hot isothermal wall and cold inclined wall) and found that the heat transfer from hot base wall to inclined cold wall is high at low pitch angles and reduces with increasing pitch angle.…”
Section: Introductionmentioning
confidence: 99%